AGO2: A New Argonaute Compromising Plant Virus Accumulation - Alvarado, Veria Y.; Scholthof, Herman B. (Frontiers in Plant Science, 2012)
Plant viruses use several strategies to transport their nucleic acid genomes throughout the plants. Regardless of the movement mechanism, a universal major block to uninterrupted viral trafficking is the induction of antiviral silencing that degrades viral RNA. To counteract this defense, viruses encode suppressors that block certain steps in the RNA silencing pathway, and consequently these proteins allow viral spread to proceed. There is a constant battle between plants and viruses and sometimes viruses will succeed and invade the plants and in other cases the RNA silencing mechanism will override the virus. A key role in the silencing versus suppression conflict between plants and viruses is played by one or more members of the ARGONAUTE protein (AGO) family encoded by plants. Here we review the mechanisms and effects of antiviral silencing with an emphasis on the contribution of AGOs, especially the recently discovered role of AGO2.